FACING DIFFERENCES AS RESOURCE OF HARMONY: A CASE IN BANGUNTAPAN - Ulumudin, Moch. Ichiyak (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2017)
Indonesia is one of the heterogeneous countries and has various diversity of language, ethnicity, tradition, and religion. Religious differences in some cases are very vulnerable to confl icts such as those that have happened in Poso and Ambon. However, religious differences will not necessarily lead to religious confl icts if it is the case in Plumbon, Banguntapan, Bantul, Yogyakarta. In the region, there are three different religions: Islam, Hinduism, Christianity and Catholicism. Nevertheless, they can live in harmony in these differences. Religious harmony in Banguntapan is formed through an interactive dialogue framed in celebrations, traditions and religious ceremonies. Each Religion is a religious ceremony. The celebration or ceremony serves as a means of dialogue by participating in it as a form of appreciation of other religions as well as supporting and conditioning the situation of celebration. On the other hand, supports are also in the form of fi nancial, moral and efforts to fi nd synergy or balance among religious people. The uniqueness in Banguntapan village is in the tradition of religious ceremonies that local people consider highly sensitive to interfaith ritual activities. Keywords: Religious Difference, Religious Harmony, Religious Rituals.